Mechanical behavior of aramid-polypropylene fiberweb composites. (15th July 2021) - Jaiswal, Gargi; Singha, Maloy K.; Das, Dipayan
Abstract: Aramid and polypropylene staple fibers were blended homogeneously at different weight percentages to prepare hybrid fiberwebs, which were processed through compression moulding technology to prepare a series of discontinuous fiberweb composites. Extensive experimental investigations were carried out to understand the stiffness, strength and failure mechanism of such composites under tension, compression, shear, bending, and impact loads. Experimental results were discussed in the light of theoretical models. A modified rule of mixture with realistic fiber orientation factor and void content predicted the tensile properties quite satisfactorily. The flexural behaviour was correlated well with the distinct material response under tension and compression.